Productivity Without Sacrificing Taste: A Case Study Of Robot Interface In Singapore Fast Food Restaurant - Mathath, Anas (2014)
The purpose of this research is to understand the application of robotic automation in a Chinese fast food restaurant in Singapore. Labor shortage is the key issue faced by Singapore food service sector. The objective of this study is to identify the potential benefits of robotic automation in restaurant and how it boosts the productivity by reducing reliance on manpower. In this study, Ruyi, a Chinese fast food restaurant has been chosen to examine the potential benefits of robotic wok for food preparation and the issues associated with the automation. The utilization of robotic wok was able to reduce the labor costs and hence raise the productivity. However, automated food preparation was unable to meet the preference of the customers. This research uses the case study method to examine the issue associated with robotic interface in the food preparation. Failure to deliver consistent quality and tasty foods was identified as the root cause of the issue as a result of inconsistent Benchmarking, Service blueprint and Tows analysis were used to answer research issues. This study proposes the appropriate use of robotic machine to design the work process without creating any odds for customer complaints. Using the benchmarking analysis, existing issues with the automation issues can be improved by following the productivity and reduce manpower after installing the semi automation. x questions posted in the study. Recommendations were put forward for the identified operation of benchmark restaurants. Tung Lok group was able to achieve work design and the absence of quality check. Analysis tools such as Ishikawa,